2022
DOI: 10.1098/rsos.211769
|View full text |Cite
|
Sign up to set email alerts
|

Differences in dogs’ event-related potentials in response to human and dog vocal stimuli; a non-invasive study

Abstract: Recent advances in the field of canine neuro-cognition allow for the non-invasive research of brain mechanisms in family dogs. Considering the striking similarities between dog's and human (infant)'s socio-cognition at the behavioural level, both similarities and differences in neural background can be of particular relevance. The current study investigates brain responses of n = 17 family dogs to human and conspecific emotional vocalizations using a fully non-invasive event-related pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 82 publications
(138 reference statements)
5
22
1
Order By: Relevance
“…The remaining five studies [10,17,60,70,99] deployed event-related potentials (ERP) frameworks to understand visual, auditory and language processing. Törnqvist et al [99] investigated the ERPs of dogs in response to human and dog faces.…”
Section: Wakefulness Eeg In Dogsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining five studies [10,17,60,70,99] deployed event-related potentials (ERP) frameworks to understand visual, auditory and language processing. Törnqvist et al [99] investigated the ERPs of dogs in response to human and dog faces.…”
Section: Wakefulness Eeg In Dogsmentioning
confidence: 99%
“…Finally, Balint et al [17] investigated the auditory processing of 17 dogs in response to human and dog vocalizations. They found that, similar to humans, dogs exhibited differential ERP responses based on the species of the vocalizer.…”
Section: Wakefulness Eeg In Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon-Fanelli et al [ 100 ] demonstrated that male dogs are predominantly prone to develop repetitive behavior (obsessing tail-chasing, chewing), aberrant sensory and social stimuli response, and impaired affective and social behavior (phobias, aggressivity, social isolation) in relation to intraspecific interaction or in relation with human. A recent study published by the Royal Society of Open Science suggested that the social and cognitive aspects of the neurobehavioral status of dogs are similar to the behavior of human infants [ 101 ].…”
Section: Autism and Schizophrenia Zebrafish Animal Modelsmentioning
confidence: 99%
“…Several studies have demonstrated that the family dog is a promising animal model for human socio-cognitive behaviors as well as their neuro-cognitive background. This includes attachment (behavior 27 ; EEG 28 ; neuroimaging 29 ), voice processing (behavior 30 ; ERP 31 ; neuroimaging 32 ) and learning (behavior 33 ; EEG 34 , 35 ). Furthermore, the family dog is increasingly recognized as a model for human neuropsychiatric conditions, such as obsessive–compulsive disorder 36 , autism 37 and ADHD-like characteristics 38 .…”
Section: Introductionmentioning
confidence: 99%